A laser‐assisted endoscopic approach to pyriform sinus fistula via fibrin glue cauterization. Issue 12 (12th December 2022) - Momii, Manami; Kawano, Toshiaki; Takakura, Sonoka; Hirano, Takashi; Tateyama, Kaori; Suzuki, Masashi
Abstract: In the past, the general treatment method for pyriform sinus fistula was its removal by open surgery; however, in recent years, endoscopic surgery has become more common. We report two cases where laser surgery was performed using an endoscope and recurrence was prevented using fibrin glue. Both cases involved 3‐year‐old girls who underwent laser ablation of a pyriform sinus fistula under an endoscope, after which the site was closed with fibrin glue. No recurrence was observed in either case, and the postoperative course was uneventful. This approach is presented as a non‐invasive and effective treatment for pyriform sinus fistula. Abstract : This paper reports the cases of endoscopic laser ablation with fibrin glue application for pyriform sinus fistula (PSF) closure. This makes a significant contribution to the literature because recurrence of PSF was prevented using fibrin glue.